Analysis of Two Translation Applications : Why is DeepL Translate more accurate than Google Translate? - Telaumbanua, Yasminar Amaerita; Marpaung, Angelin; Gulo, Ceria Putri Damai; Waruwu, Dodi Kardo Wijaya; Zalukhu, Erika; Zai, Novita Purnawirati (Yayasan Kita Menulis, 2024)
DeepL Translate and Google Translate are two leading machine translation tools. The focus of this research is to analyze the accuracy of translation results provided by DeepL Translation and Google Translation specifically in translating English to Indonesian. This research used a qualitative approach of document analysis and interviews. The advanced neural machine translation technology of DeepL, by utilizing extensive data, enables it to recognize language nuances and provide contextually accurate translations. In contrast, Google Translate, despite having grown to be supported by hundreds of languages, often struggles with complex sentences and idiomatic expressions. DeepL's accuracy and natural-sounding translations make it a top choice for professional and detailed translations. The study concludes that DeepL's focus on quality and accuracy, rather than the breadth of language support, makes it a more reliable translation tool.